UPAYA PENINGKATAN PARTISIPASI BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA EVALUASI INTERAKTIF PADA MATERI WAWASAN NUSANTARA DI KELAS VIII C SMPN 19 MALANG - Ester Dewi Barek Goran; Andri Fransiskus Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student learning participation is one of the key factors in achieving successful learning outcomes. However, conditions observed in class VIII C of SMPN 19 Malang revealed that most students remained passive, lacked initiative in expressing their opinions, and had not been optimally engaged during group discussions. This condition occurred almost every time the learning process took place, particularly in Civic Education (PPKn) lessons. Therefore, this study was important to conduct, aiming to describe the implementation of the Problem Based Learning (PBL) model assisted by interactive evaluation media and to analyze the improvement in students' learning participation on Wawasan Nusantara material. This study employed a Classroom Action Research (CAR) approach using the Kemmis McTaggart model, carried out in two cycles involving 32 students of class VIII C in the even semester. Data were collected through observation, tests, and documentation. The findings showed consistent progress at each stage, with the average percentage of learning participation rising from 42.32% in the pre-cycle to 65.11% in Cycle I, and reaching 84.38% in Cycle II. As these results exceeded the predetermined success indicator of ≥75%, the implementation of the PBL model assisted by interactive evaluation media was concluded to be effective in improving students' learning participation on Wawasan Nusantara material